An assessment of the University of the Philippines Los Baños BS Human Ecology Academic Program from 1978-2012 - Sandalo, Ricardo M. (Journal of Human Ecology, 2012)
Two hundred and six (206) BS Human Ecology (BSHE) alumni of the University of the Los Baños (UPLB) College of Human Ecology (CHE) served the respondents of the study. The research (1)determined the employment and employability of the BSHE graduates in terms of relevance of human ecology to the jobs, time spent in securing their first job, salary, tenure, job type, type of employer/sector and workplace; (2) examined factors affecting the respondents' employability which included useful skills/knowledge acquired during and after college, core competencies of graduates, perceptions of employers and public awareness regarding CHE's objectives and thrusts and the aims of human ecology as a discipline and as a profession; and (3)gathered feedback from the graduates on ways to improve the implementation of the BSHE program. The respondents accomplished self-administered questionnaires. Data were then encoded and analyzed using frequency counts and percentages. The study found that other determinants of employability of BSHE graduates included skills/knowledge acquired and the major which the respondents took during college, the postgraduate course/training pursued and the public's awareness and prospective employers' knowledge on human ecology and the capabilities of a human ecology graduate.